Gender differences in perceived legitimacy and status perception in leadership role - Cha, Hyunjin; Uchida, Yukiko; Choi, Eunsoo (Frontiers in Psychology, 2023)
The present study examined the difference between women and men in perceiving leadership roles. Two experiments, one online and the other experimental, investigated the subjective experiences of Japanese men and women when they are assigned different roles (e.g., leader vs. subordinate). Both studies revealed that women perceived their roles as less legitimate when assigned leader roles (vs. subordinate roles). In contrast, regardless of the assigned roles, men did not differ in their perceived legitimacy. This discrepancy between men and women in their legitimacy perception of different roles showed a significant variance in women’s lower sense of status when they were a leader (vs. subordinate), but not among men. Our study results illustrate the psychological barrier challenging women in organizations that are embedded in a cultural context in which women leaders are highly underrepresented.